Peran Ganda Perempuan dalam Keluarga Pespektif Feminis Muslim Indonesia - Zahra Zaini Arif (Indonesian Journal of Islamic Law, 2018)
This article examines the dual role of women in the family from the perspective of Indonesian Muslim feminists. The focus of the study is on how Muslim feminists in Indonesia construct their ideas about women’s dual roles within the family and what implications these ideas have for women and family life. The issue of women’s dual roles has become a prominent topic alongside the emergence of various typologies of Indonesian Muslim feminism. These feminist typologies analyze women’s dual roles according to their respective perspectives as groups seeking to promote equality and mutual understanding of the positions of men and women within the family. Several feminist groups in Indonesia offer distinct viewpoints that shape the implications of women’s dual burden between domestic and public spheres. These feminist activists represent different intellectual constructions regarding the roles of Indonesian Muslim women, situated between domestic and public domains. Women’s dual roles are widely discussed and studied in order to identify an ideal position for women within the context of Indonesian families. This research aims to determine the ideal role of women in the Indonesian family context. The study employs a conceptual approach and a historical approach, both of which fall within qualitative research, and uses library research by focusing on primary and secondary sources. The findings indicate that: (1) Indonesian Muslim feminists’ views on women’s dual roles are divided into three positions—those who support the dual role, those who reject it, and those who argue that women’s dual roles should be adjusted to the respective responsibilities of men and women within the family; and (2) the implications of these feminist discourses are the diversity of perspectives, which in turn produce diverse patterns of women’s participation in the public sphere, so that women’s position in social progress within the Indonesian context remains contested. Women’s involvement in the public sphere cannot be separated from their roles as mothers and partners to their husbands, with continued emphasis on women’s responsibility for managing internal household affairs. Consequently, women remain primarily responsible for internal family roles as mothers and spouses.